Reimagining Smart Governance in Digital Periphery: Papua and West Papua Comparison Studies - Hanif, Nita Aribah; Atmojo, Muhammad Eko; Hakim, Muhammad Lukman (JURNAL TRIAS POLITIKA, 2025)
This study aims to enhance the smart governance performance in the Papua and West Papua Governments in their current condition, especially on the website and platform X. The method of this study is qualitative with a case study approach. The data collected through the documentation technique based on the website and X account of the Papua and West Papua Governments, official government data, online mass media and previous studies literature. This study found that the smart governance in the Papua and West Papua Governments is not optimal and requires improvement in public service, transparency, and public participation indicators. Several challenges of smart governance implementation in both local governments are the infrastructure limitations, low digital literacy capability, and internet signal inclusivity. This study has several suggestions to improve the smart governance performance in the Papua and West Papua Governments. (1) The Papua and West Papua Governments must prioritize digital training for the bureaucracy to enhance digital literacy in the government. (2) The Papua and West Papua Governments are also required to improve their education curriculum to include digital skills for students. Further research is proposed to map the citizens sentimental perception about smart governance in both local governments by social media analysis